2007
DOI: 10.1182/blood-2007-04-087056
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of ex vivo–expanded mesenchymal stem cells accelerates lymphocyte recovery and may reduce the risk of graft failure in haploidentical hematopoietic stem-cell transplantation

Abstract: Haploidentical hematopoietic stem-cell transplantation (HSCT) is associated with an increased risk of graft failure. Adult bone marrow-derived mesenchymal stromal cells (MSCs) have been shown to support in vivo normal hematopoiesis and to display potent immune suppressive effects. We cotransplanted donor MSCs in 14 children undergoing transplantation of HLA-disparate CD34 ؉ cells from a relative. While we observed a graft failure rate of 15% in 47 historic controls, all patients given MSCs showed sustained hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
380
2
10

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(400 citation statements)
references
References 9 publications
8
380
2
10
Order By: Relevance
“…Although their immunomodulatory properties are not yet completely understood, their low immunogenic potential, together with their effects on immune responses, make them a promising therapeutic tool for severe refractory autoimmune diseases. MSCs have already been used in clinical trials as a treatment for acute graft-versus-host disease following allogeneic HSCT (25,26) and for autoimmune diseases such as systemic sclerosis (27) and type 1 diabetes mellitus (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although their immunomodulatory properties are not yet completely understood, their low immunogenic potential, together with their effects on immune responses, make them a promising therapeutic tool for severe refractory autoimmune diseases. MSCs have already been used in clinical trials as a treatment for acute graft-versus-host disease following allogeneic HSCT (25,26) and for autoimmune diseases such as systemic sclerosis (27) and type 1 diabetes mellitus (28).…”
Section: Discussionmentioning
confidence: 99%
“…Bernardo et al 96 used MSCs at the time of HSCT transplantation in children who were recipients of cord blood grafts. Ball et al 97 performed co-transplantation of MSCs in children undergoing haploidentical HSCT. Compared with retrospective controls, they saw less graft failure and faster engraftment of platelets using MSCs.…”
Section: Stromal Cells For Prevention Of Gvhdmentioning
confidence: 99%
“…[22][23][24] After haploidentical SCT, co-transplantation with MSCs enhanced NK-cell but not neutrophil or platelet recovery. 25 In vitro, MSCs have antiproliferative properties that target virtually all types of immune cells. Accordingly, human MSCs suppress lymphocyte alloreactivity when added in MLRs.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…26,27 Co-infusion of MSCs reduced the incidence of graft failure and rejection in preliminary clinical trials. 24,25 In a phase-I study, the incidence of acute GVHD grade II-IV was observed in 28% of patients co-administered with culture-expanded MSCs and HLA-identical sibling-matched HSCs. 23 However, whether MSCs exert preventive effects on the development of GVHD as well as therapeutic effects in established GVHD needs to be evaluated in prospective clinical trials.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%